2002
DOI: 10.1002/per.450
|View full text |Cite
|
Sign up to set email alerts
|

Replicable types and subtypes of personality: Spanish NEO‐PI samples

Abstract: Three major personality prototypes were derived on the basis of a Big Five instrument (NEO‐PI) by means of replicated cluster analysis in two Spanish samples (a sample from the general population and a student sample). The replicability of the three prototypes within and their consistency between the two samples were evaluated. In addition, subtypes were analysed in a similar way. Finally, the relation between prototype assignment and level of education was examined in the sample from the general population. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 13 publications
2
22
0
6
Order By: Relevance
“…Our findings are consistent with past literature indicating separate overcontrolled and undercontrolled brittle personality types (Asendorpf et al, 2001;Asendorpf & van Aken, 1999;Boehm, Asendorpf, & Avia, 2002;Caspi & Silva, 1995;Pulkkinen, 1996;Robins et al, 1996;Schnabel et al, 2002;York & John, 1992). Also consistent with our findings, virtually all of these studies have indicated that the brittle overcontrolled group suffers greater psychological maladjustment than its undercontrolled counterpart.…”
Section: Comparability To Previous Research On Personality Typessupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings are consistent with past literature indicating separate overcontrolled and undercontrolled brittle personality types (Asendorpf et al, 2001;Asendorpf & van Aken, 1999;Boehm, Asendorpf, & Avia, 2002;Caspi & Silva, 1995;Pulkkinen, 1996;Robins et al, 1996;Schnabel et al, 2002;York & John, 1992). Also consistent with our findings, virtually all of these studies have indicated that the brittle overcontrolled group suffers greater psychological maladjustment than its undercontrolled counterpart.…”
Section: Comparability To Previous Research On Personality Typessupporting
confidence: 83%
“…The methodology of the present study also differed from work by Asendorpf and his colleagues (Asendorpf & van Aken, 1999;Asendorpf et al, 2001;Boehm et al, 2002;Schnabel et al, 2002). In particular, our cluster analysis was based on two scales: egoresilience and ego-control.…”
Section: Comparability To Previous Research On Personality Typesmentioning
confidence: 66%
See 1 more Smart Citation
“…Uprkos tome što pojedina istraživanja ukazuju na robusnost tri velika tipa ličnosti u različitim kulturama (Klimstra, Hale, Raaijmakers, Branje, & Meeus, 2010;Robins et al, 1996), postoje uporediva istraživanja koja beleže različite profile u različitim kulturama (Boehm et al, 2002;Schnabel et al, 2002). Takođe, ima rezultata koji sugerišu da se profili tri klastera razlikuju od "prototipskih".…”
unclassified
“…Kritike se odnose na problem medija procene, odnosno na pitanje da li su samo jedan model ličnosti i samo jedan domen procene dovoljni za adekvatnu procenu stabilnosti tipova (Roth & Herzberg, 2007;van Leeuwen, de Fruyt, & Mervielde, 2004), potom na uzorak (Boehm et al, 2002;Costa et al, 2002;van Leeuwen et al, 2004), ali i na metode obrade podataka. Jedna od ključnih zamerki koje se odnose na metode obrade podataka je izostanak primene metoda samouzorkovanja (engl.…”
unclassified